Soil nitrogen pools and turnover in native woodland and managed pasture soils. (June 2015) - Prendergast-Miller, Miranda T.; de Menezes, Alexandre B.; Farrell, Mark; Macdonald, Lynne M.; Richardson, Alan E.; Bissett, Andrew; Toscas, Peter; Baker, Geoff; Wark, Tim; Thrall, Peter H.
Abstract: Dissolved organic nitrogen (DON) is a significant nitrogen (N) pool in most soils and is considered to be important for N cycling. The present study focused on paired sites of native remnant woodland and managed pasture at three locations in south-eastern Australia. Improved understanding of N cycling is important for assessing the impact of agriculture on soil processes and can guide conservation and restoration soil management strategies to maintain remnant native woodland systems, which currently exist as small pockets of woodland within extensive managed pasture landscapes. Organic and inorganic N pools were quantified, as well as the rates of amino acid and peptide mineralisation in the paired native woodland and managed pasture systems. Soil DON dominated the soil N pool in both land uses, and the proportion of DON to other N pools was greatest at the most N-limited site (up to ∼70% of extractable N). In both land uses soil ammonium and free amino acid concentrations were similar (∼20% of extractable N), and soil nitrate formed the smallest N pool (<∼5% of extractable N). Mineralisation of 14 C-labelled amino acid and peptide substrates was rapid (<3 h), and more amino acid was respired than peptide in both the native woodland and managed pasture soils. Soil C:N ratio was important in separating site and land use differences, and contrasting relationships between soil physico-chemical properties and organic N uptake rates were identified across sites and land uses. Highlights: Soil N pools quantified in native woodland and pasture soils in SE Australia. Soil microbial mineralisation of 14 C-alanine and tri-alanine was measured. Microbial mineralisation of added substrates was rapid (<3 h) in both land uses.